What the Old Testament authors really cared about : a survey of Jesus' Bible - DeRouchie, Jason S. (Shane) (Grand Rapids, MI. Kregel Academic, 2013)
"Arranged in the order of Jesus' Jewish Bible and with helpful, one-page snapshots of essential information, this Old Testament survey has 13 maps, 80 charts, over 160 side-bars, and nearly 200 color photographs."
Keywords: Bible.-- Old Testament; Bible.-- Old Testament.-- Introductions